Microcirculation physiotherapy pad
Patent Information
- Application Number
- CN202411617158.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-11-13
AI Technical Summary
[0003]理疗垫使用时,通常需要躺在床垫上进行改善,因此与理疗垫需要接触较长的时间,且一般理疗垫需要加热使用,以达到更好的理疗效果,但是长时间使用,与理疗垫长时间接触,人的肢体与面料与理疗垫表面不断摩擦,很容易出现面料破损等现象,使得理疗垫的使用舒适度下降,故有待改善
1.在面料组件的石墨烯空气层表面涂覆耐磨涂料,使得石墨烯空气层的表面形成一层耐磨层,耐磨涂料中耐磨组份具有芳纶纤维、多巴胺与纳米二氧化硅组份,能够起到良好的耐磨性能,能够协同提升耐磨涂料整体的机械性能,并且得到的耐磨层能够具有良好的耐磨性能,从而提升了理疗垫整体的使用寿命;
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of mattresses, and more particularly to a microcirculation therapy mat. Background Technology
[0002] A physiotherapy mat is a type of mattress that can promote blood circulation and improve microcirculation. When the body experiences fatigue, muscle tension, or other discomfort, a physiotherapy mat can be used to provide appropriate relief and improve these symptoms.
[0003] When using a physiotherapy pad, one usually needs to lie on a mattress for relief, which requires a relatively long period of contact with the pad. Generally, physiotherapy pads need to be heated to achieve better therapeutic effects. However, with prolonged use and contact with the pad, the constant friction between the limbs and the pad's surface can easily cause damage to the fabric, reducing the comfort of using the pad. Therefore, this needs to be improved. Summary of the Invention
[0004] To improve the wear resistance of physiotherapy pads, this application provides a microcirculation physiotherapy pad.
[0005] The microcirculation therapy pad provided in this application adopts the following technical solution: A microcirculation therapy pad includes a therapy component and a fabric component. The fabric component covers the outside of the therapy component and includes a wear-resistant layer, a graphene air layer, a graphene fiber layer, a silk-like cotton layer, a brushed fabric layer, a needle-cotton layer, a sponge layer, and a mesh breathable layer. The therapy component is located between the brushed fabric and the needle-cotton fabric. The wear-resistant layer is formed by coating the surface of the graphene air layer with a wear-resistant coating, and the wear-resistant coating includes the following components in parts by weight: 500-560 parts of coating substrate, 60-70 parts of antibacterial sustained-release microcapsules, 120-160 parts of abrasion-resistant component, 12-16 parts of softener, and 10-16 parts of defoamer; The wear-resistant components include aramid fibers, dopamine, and silica.
[0006] By adopting the above technical solution, using the graphene air layer and graphene fiber layer as the outer layer of the fabric component, it can achieve moisture absorption and perspiration wicking, antistatic and antibacterial effects, thereby promoting the effect of the physiotherapy pad. Moreover, the above-mentioned fabric layer has moderate softness and hardness and excellent breathability, which can effectively improve the comfort during use. At the same time, the surface of the graphene air layer is coated with a wear-resistant coating to form a wear-resistant coating on the surface of the graphene air layer, which can reduce the wear of the graphene air layer fabric and thus extend the service life of the physiotherapy pad. The wear-resistant component in the wear-resistant coating is prepared by compounding dopamine, aramid fiber and silica, which can give the wear-resistant component good compatibility. Coating dopamine on the surface of aramid fiber to obtain nano-units, and after silica is generated on the surface, a wear-resistant component with hydrophobic properties is obtained, which improves the wear resistance and the overall mechanical properties of the coating.
[0007] Preferably, the wear-resistant component is prepared by the following method: Nano-aramid fibers were mixed with deionized water to obtain an aramid fiber dispersion. Dopamine was added to adjust the pH to alkaline, and the mixture was stirred and reacted. After the reaction, the mixture was washed to obtain dopamine-modified aramid fibers. The dopamine-modified aramid fibers were then mixed with anhydrous ethanol, ammonia was added, and the mixture was sonicated. While stirring, the temperature was increased, and tetraethyl orthosilicate and 1H,1H,2H,2H-perfluorodecyltriethoxysilane were added. The mixture was stirred for 4 hours, and then 1H,1H,2H,2H-perfluorodecyltriethoxysilane was added again. The mixture was stirred and reacted for 3 hours to obtain the wear-resistant component.
[0008] By adopting the above technical solution, dopamine is coated on the surface of aramid fiber, and nano-silica particles are grown in situ on the surface through tetraethyl orthosilicate. Low surface energy modification is performed using 1H,1H,2H,2H-perfluorodecyltriethoxysilane, which gives the component superhydrophobic properties. As a result, the prepared wear-resistant component has good wear resistance and mechanical properties, as well as good hydrophobic properties, which gives the prepared physiotherapy pad good wear resistance and breathability.
[0009] Preferably, the mass ratio of the aramid fiber to dopamine is 1:(1.12-1.18).
[0010] By adopting the above technical solution, and preferably having the mass ratio of dopamine to aramid fiber within the above range, the stability of the prepared dopamine-modified aramid fiber can be further improved.
[0011] Preferably, the mass ratio of the dopamine-modified aramid fiber to tetraethyl orthosilicate is 1:(0.45-0.49).
[0012] By adopting the above technical solution, and preferably within the above range the mass ratio of dopamine-modified aramid fiber to tetraethyl orthosilicate, the stability of the prepared dopamine-modified aramid fiber can be further improved.
[0013] Preferably, the antibacterial sustained-release microcapsules comprise daylily fragrance, polyvinyl alcohol, and ε-polylysine.
[0014] Preferably, the antibacterial sustained-release microcapsules are prepared by the following method: Daylily fragrance was mixed with isophorone diisocyanate to obtain an oil phase. Polyvinyl alcohol was mixed with deionized water to obtain a polyvinyl alcohol dispersion. The polyvinyl alcohol dispersion was heated to the reaction temperature, and the oil phase was added to the polyvinyl alcohol dispersion. Emulsifiers and chain extenders were added and stirred to obtain a daylily fragrance pre-microcapsule emulsion. ε-polylysine was mixed with deionized water to obtain an ε-polylysine aqueous solution. The ε-polylysine aqueous solution was added to the daylily fragrance pre-microcapsule emulsion, and the reaction was carried out while maintaining the reaction temperature and stirring to obtain antibacterial sustained-release microcapsules.
[0015] By adopting the above technical solution, the volatile components in daylily fragrance are beneficial to human health. When combined with a therapeutic pad, it can further enhance the effect of promoting human circulation. At the same time, it has an antibacterial effect and can work synergistically with graphene fabric to inhibit bacteria. By preparing microcapsules with ε-polylysine and polyvinyl alcohol to encapsulate daylily fragrance, the daylily fragrance can be released slowly, and the phenomenon of rapid oxidation and inactivation of daylily fragrance can be reduced, so that daylily fragrance can play a long-term role. Moreover, the surface roughness of the prepared microcapsules is improved, which can stably adhere to the fiber surface, thereby improving the stability of the antibacterial slow-release microcapsules and maintaining the breathability of the fabric, keeping the fabric comfortable.
[0016] Preferably, the mass ratio of daylily fragrance, polyvinyl alcohol and ε-polylysine is 1:1.1:(0.69-0.75).
[0017] By adopting the above technical solution, and optimizing the mass ratio of daylily fragrance, polyvinyl alcohol and ε-polylysine within the above range, the overall performance of the prepared antibacterial sustained-release capsules can be further improved.
[0018] Preferably, the emulsifier includes Tween-80.
[0019] Preferably, the reaction temperature is 50-60℃.
[0020] Preferably, the wear-resistant coating is prepared by the following method: The coating substrate, antibacterial slow-release microcapsules, abrasion-resistant components, softener and defoamer are mixed and stirred to obtain an abrasion-resistant coating.
[0021] In summary, this application includes at least one of the following beneficial technical effects: 1. A wear-resistant coating is applied to the surface of the graphene air layer of the fabric component, so that a wear-resistant layer is formed on the surface of the graphene air layer. The wear-resistant components in the wear-resistant coating include aramid fiber, dopamine and nano silica, which can play a good wear-resistant role and can synergistically improve the overall mechanical properties of the wear-resistant coating. The resulting wear-resistant layer has good wear resistance, thereby improving the overall service life of the physiotherapy pad. 2. The wear-resistant filler also contains antibacterial sustained-release microcapsules, which are prepared by daylily fragrance, ε-polylysine and polyvinyl alcohol. Daylily fragrance has good antibacterial effect and its volatile components are beneficial to promoting human circulation. Encapsulating daylily fragrance in the microcapsule structure allows the daylily fragrance to be released slowly. On the one hand, the antibacterial sustained-release microcapsules can have a synergistic antibacterial effect with the graphene air layer and graphene fiber layer. On the other hand, it can also further promote the effect of the therapeutic pad on promoting human circulation. Detailed Implementation
[0022] The present application will be further described in detail below with reference to the embodiments: Material specifications: The coating substrate is water-based polyurethane; the emulsifier is Tween-80; the chain extender is an 8% (w / w) ethylene glycol ethanol solution; the softener is polyethylene glycol; the defoamer is a polysiloxane defoamer; and the daylily fragrance was purchased from Chengdu Pusi Biotechnology Co., Ltd.
[0023] Example 1 Preparation of wear-resistant components: 6.13 g of nano-aramid fibers were mixed with 500 g of deionized water to obtain an aramid fiber dispersion. 6.87 g of dopamine (CAS No.: 51-61-6) was added, and the pH was adjusted to 8.5 using Tris buffer. The mixture was magnetically stirred at 600 rpm for 24 h at 25 °C. After the reaction, the fibers were washed three times with anhydrous ethanol to obtain dopamine-modified aramid fibers. 12.12 g of dopamine-modified aramid fibers were mixed with 300 g of anhydrous ethanol... After mixing, 15g of ammonia water was added, and the mixture was sonicated for 30 minutes. Then, while stirring magnetically at 600 rpm, the temperature was increased to 30°C. While maintaining the stirring conditions, 7.88g of tetraethyl orthosilicate and 2.3g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane (CAS No.: 101947-16-4) were added, and the mixture was stirred for 4 hours. Then, 0.2g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane was added, and the mixture was stirred for 3 hours to obtain the wear-resistant component.
[0024] Preparation of antibacterial sustained-release microcapsules: 5.38g of daylily fragrance and 2.69g of isophorone diisocyanate (CAS No.: 4098-71-9) were mixed to obtain an oil phase. 5.91g of polyvinyl alcohol (CAS No.: 9002-89-5) and 150g of deionized water were mixed and stirred to obtain a polyvinyl alcohol dispersion. The polyvinyl alcohol dispersion was heated to 50℃, and the oil phase was added to the polyvinyl alcohol dispersion. 7g of emulsifier and 5g of chain extender were added, and the mixture was stirred at 600rpm for 90min to obtain a pre-made microcapsule emulsion of daylily fragrance. 3.71g of ε-polylysine (CAS No.: ε-polylysine) and 37g of deionized water were mixed to obtain an aqueous solution of ε-polylysine. The aqueous solution of ε-polylysine was added to the pre-made microcapsule emulsion of daylily fragrance, and the mixture was stirred at 600rpm for 90min while maintaining a temperature of 50℃ to obtain antibacterial sustained-release microcapsules.
[0025] Preparation of wear-resistant coatings: Mix 500g of coating substrate, 60g of antibacterial slow-release microcapsules, 120g of abrasion-resistant component, 12g of softener and 10g of defoamer, and stir at 900rpm for 45min to obtain abrasion-resistant coating.
[0026] Preparation of the therapy pad: The graphene air layer is completely immersed in the wear-resistant coating, ensuring full contact between the coating and the air layer. After soaking for 2 hours, the graphene air layer is dried at 45°C for 4 hours, resulting in a wear-resistant layer on its surface. The graphene air layer with the wear-resistant layer, graphene fiber layer, imitation silk cotton layer, brushed fabric layer, needle cotton layer, sponge layer, and fishing net breathable layer are then stacked sequentially. After sewing together three adjacent sides, a fabric component preform is obtained. After finishing, the unsewn fabric component preform of the physiotherapy component is filled between the brushed fabric layer and the needle cotton layer. After finishing, the fabric component preform is sewn together, covering the physiotherapy component with the fabric component, resulting in the physiotherapy pad product.
[0027] Example 2 Preparation of wear-resistant components: 5.96g of nano-aramid fiber was mixed with 500g of deionized water to obtain an aramid fiber dispersion. 7.04g of dopamine was added, and the pH was adjusted to 8.5 using Tris buffer. The mixture was magnetically stirred at 600rpm for 24h at 25℃. After the reaction, the mixture was washed three times with anhydrous ethanol to obtain dopamine-modified aramid fiber. 11.83g of dopamine-modified aramid fiber was mixed with 300g of anhydrous ethanol, and 15g of ammonia was added. After sonication for 30min, the mixture was magnetically stirred at 600rpm while the temperature was increased to 30℃. 8.17g of tetraethyl orthosilicate and 2.3g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane were added while maintaining stirring. The mixture was stirred for another 4h, and then 0.2g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane was added. The mixture was stirred for another 3h to obtain the wear-resistant component.
[0028] Preparation of antibacterial sustained-release microcapsules: 5.26g of daylily fragrance and 2.63g of isophorone diisocyanate were mixed to obtain an oil phase. 5.79g of polyvinyl alcohol and 150g of deionized water were mixed and stirred to obtain a polyvinyl alcohol dispersion. The polyvinyl alcohol dispersion was heated to 60℃, and the oil phase was added to the polyvinyl alcohol dispersion. 7g of emulsifier and 5g of chain extender were added, and the mixture was stirred at 600rpm for 90min to obtain a daylily fragrance pre-microcapsule emulsion. 3.95g of ε-polylysine and 40g of deionized water were mixed to obtain an ε-polylysine aqueous solution. The ε-polylysine aqueous solution was added to the daylily fragrance pre-microcapsule emulsion, and the mixture was stirred at 60℃ for 90min to obtain antibacterial sustained-release microcapsules.
[0029] Preparation of wear-resistant coatings: Mix 560g of coating substrate, 70g of antibacterial slow-release microcapsules, 160g of abrasion-resistant component, 16g of softener and 16g of defoamer, and stir at 900rpm for 45min to obtain abrasion-resistant coating.
[0030] Preparation of the therapy pad: The graphene air layer is completely immersed in the wear-resistant coating, ensuring full contact between the coating and the air layer. After soaking for 2 hours, the graphene air layer is dried at 45°C for 4 hours, resulting in a wear-resistant layer on its surface. The graphene air layer with the wear-resistant layer, graphene fiber layer, imitation silk cotton layer, brushed fabric layer, needle cotton layer, sponge layer, and fishing net breathable layer are then stacked sequentially. After sewing together three adjacent sides, a fabric component preform is obtained. After finishing, the unsewn fabric component preform of the physiotherapy component is filled between the brushed fabric layer and the needle cotton layer. After finishing, the fabric component preform is sewn together, covering the physiotherapy component with the fabric component, resulting in the physiotherapy pad product.
[0031] Example 3 Preparation of wear-resistant components: 6.05g of nano-aramid fiber was mixed with 500g of deionized water to obtain an aramid fiber dispersion. 6.95g of dopamine was added, and the pH was adjusted to 8.5 using Tris buffer. The mixture was magnetically stirred at 600rpm at 25℃ for 24h. After the reaction, the mixture was washed three times with anhydrous ethanol to obtain dopamine-modified aramid fiber. 11.98g of dopamine-modified aramid fiber was mixed with 300g of anhydrous ethanol, and 15g of ammonia was added. After sonication for 30min, the mixture was magnetically stirred at 600rpm while the temperature was increased to 30℃. 8.02g of tetraethyl orthosilicate and 2.3g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane were added while maintaining stirring. The mixture was stirred for another 4h, and then 0.2g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane was added. The mixture was stirred for another 3h to obtain the wear-resistant component.
[0032] Preparation of antibacterial sustained-release microcapsules: 5.32g of daylily fragrance and 2.66g of isophorone diisocyanate were mixed to obtain an oil phase. 5.85g of polyvinyl alcohol and 150g of deionized water were mixed and stirred to obtain a polyvinyl alcohol dispersion. The polyvinyl alcohol dispersion was heated to 55℃, and the oil phase was added to the polyvinyl alcohol dispersion. 7g of emulsifier and 5g of chain extender were added, and the mixture was stirred at 600rpm for 90min to obtain a pre-made microcapsule emulsion of daylily fragrance. 3.83g of ε-polylysine and 39g of deionized water were mixed to obtain an aqueous solution of ε-polylysine. The aqueous solution of ε-polylysine was added to the pre-made microcapsule emulsion of daylily fragrance, and the mixture was stirred at 600rpm for 90min while maintaining a temperature of 55℃ to obtain antibacterial sustained-release microcapsules.
[0033] Preparation of wear-resistant coatings: Mix 530g of coating substrate, 65g of antibacterial slow-release microcapsules, 140g of abrasion-resistant component, 14g of softener and 13g of defoamer, and stir at 900rpm for 45min to obtain abrasion-resistant coating.
[0034] Preparation of the therapy pad: The graphene air layer is completely immersed in the wear-resistant coating, ensuring full contact between the coating and the air layer. After soaking for 2 hours, the graphene air layer is dried at 45°C for 4 hours, resulting in a wear-resistant layer on its surface. The graphene air layer with the wear-resistant layer, graphene fiber layer, imitation silk cotton layer, brushed fabric layer, needle cotton layer, sponge layer, and fishing net breathable layer are then stacked sequentially. After sewing together three adjacent sides, a fabric component preform is obtained. After finishing, the unsewn fabric component preform of the physiotherapy component is filled between the brushed fabric layer and the needle cotton layer. After finishing, the fabric component preform is sewn together, covering the physiotherapy component with the fabric component, resulting in the physiotherapy pad product.
[0035] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in Example 4, when preparing dopamine-modified aramid fibers, 6.34g of nano-aramid fibers and 6.66g of dopamine were used.
[0036] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in Example 5, when preparing dopamine-modified aramid fibers, 5.78g of nano-aramid fibers and 7.22g of dopamine were used.
[0037] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that in Example 6, when preparing the wear-resistant component, 12.5g of dopamine-modified aramid fiber and 7.5g of tetraethyl orthosilicate were used.
[0038] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that in Example 7, when preparing the wear-resistant component, 10.87g of dopamine-modified aramid fiber and 9.13g of tetraethyl orthosilicate were used.
[0039] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that in Example 8, when preparing the antibacterial sustained-release microcapsules, the amount of daylily fragrance used is 5.56g, polyvinyl alcohol is 6.11g, and ε-polylysine is 3.33g.
[0040] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that in Example 9, when preparing the antibacterial sustained-release microcapsules, the amount of daylily fragrance used is 5.1g, polyvinyl alcohol is 5.61g, and ε-polylysine is 4.29g.
[0041] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that the reaction temperature in Example 10 is 45°C when preparing the antibacterial sustained-release microcapsules.
[0042] Example 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that the reaction temperature in Example 11 is 65°C when preparing the antibacterial sustained-release microcapsules.
[0043] Example 12 Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that in Example 12, the daylily fragrance pre-made microcapsule emulsion is used as a sustained-release antibacterial microcapsule.
[0044] Comparative Example 1 Comparative Example 1 is based on Example 3. In Comparative Example 1, the wear-resistant component was prepared by ultrasonically dispersing dopamine-modified aramid fibers with anhydrous ethanol.
[0045] Performance testing The following performance tests were conducted on the physiotherapy pads prepared in Examples 1-12 and Comparative Example 1: (1) Wear resistance test Using ISO 5981-2007 as the testing standard, the abrasion resistance of the side of the sample with the abrasion layer was tested. Each sample was tested three times, and the average value was taken. The test results were recorded in Table 1.
[0046] (2) Hydrophobicity test The contact angle of the sample with the wear-resistant layer was tested using a five-point sampling method. Each sample was tested three times, and the average value was taken. The test results were recorded in Table 1.
[0047] (3) Antibacterial performance test Using GB / T 20944.3-2008 Evaluation of antibacterial properties of textiles as the test standard, the antibacterial performance of the side of the sample with the abrasion-resistant layer was tested. The antibacterial rate of the sample was measured after 1 day and 7 days. Each sample was tested three times, and the average value was taken. The test results were filled in Table 1.
[0048] Table 1 Performance test results of Examples 1-13 and Comparative Example 1
[0049] Data Analysis As shown in Table 1, the abrasion resistance of Examples 1-3 is 6600 cycles or more, indicating that the physiotherapy pad prepared in this application has good abrasion resistance. The contact angle of Examples 1-3 is 160° or more, indicating that the physiotherapy pad prepared in this application has good hydrophobic properties. The antibacterial rate of Escherichia coli and Staphylococcus aureus in Examples 1-3 is 99.5% or more, indicating that the physiotherapy pad prepared in this application has good antibacterial properties. After 7 days of curing, the antibacterial rate of Escherichia coli and Staphylococcus aureus in Examples 1-3 is 94% or more, indicating that the physiotherapy pad prepared in this application has long-lasting antibacterial properties.
[0050] In Examples 4 and 5, the mass ratio of nano-aramid fibers to dopamine in the preparation of dopamine-modified aramid fibers was not within the range specified in this application. When the dopamine content was too high, the dopamine layer coating the surface of the aramid fibers was too thick, making it difficult to exhibit the mechanical properties of the nano-aramid fibers. When the dopamine content was too low, it was difficult to uniformly coat the surface of the nano-aramid fibers with a dopamine layer, which affected the subsequent growth of nano-silica and the overall performance of the wear-resistant component. Therefore, the various properties of Examples 4 and 5 were reduced.
[0051] In Examples 6 and 7, the dopamine-modified aramid fibers and tetraethyl orthosilicate used in preparing the wear-resistant components were not within the scope defined in this application. When the content of tetraethyl orthosilicate was too low, the uniformity of the nano-silica particles grown on the surface of the dopamine layer decreased, and the surface roughness was too small, affecting the hydrophobic properties and stability. When the content of tetraethyl orthosilicate was too high, too many nano-silica particles were generated on the surface of the dopamine layer, affecting the dispersion performance of the wear-resistant components and further affecting the stability of the wear-resistant coating. Therefore, all properties of Examples 6 and 7 decreased.
[0052] In Examples 8 and 9, the mass ratios of daylily fragrance, polyvinyl alcohol, and ε-polylysine in the preparation of antibacterial sustained-release microcapsules were not within the range specified in this application. When the content of ε-polylysine was too low, the modification effect on the microcapsules was weak, the surface smoothness of the microcapsules was high, and the adhesion between the microcapsules and the fabric was poor, thus affecting the stability of the antibacterial sustained-release capsules. When the content of ε-polylysine was too high, the particle size of the prepared antibacterial sustained-release microcapsules was too large, resulting in inconsistent particle sizes and affecting the stability of the antibacterial sustained-release microcapsules. Therefore, the performance of Examples 8 and 9 was reduced.
[0053] In Examples 10 and 11, the reaction temperatures during the preparation of antibacterial sustained-release microcapsules were outside the range specified in this application. When the reaction temperature was too low, the components were difficult to disperse, resulting in poor interfacial polymerization and affecting the stability of the antibacterial sustained-release microcapsules. When the reaction temperature was too high, the reactions in the system were too fast, inhibiting the formation of macromolecular polymers and thus affecting the preparation of the antibacterial sustained-release microcapsules. Therefore, the performance of Examples 10 and 11 was reduced.
[0054] Example 12 did not use ε-polylysine to modify the pre-made microcapsules of daylily fragrance. On the one hand, the surface smoothness of the pre-made microcapsules of daylily fragrance was difficult to improve, and the binding effect between them and the fabric fibers was reduced. On the other hand, without the addition of ε-polylysine, it was difficult to further protect the daylily fragrance, the thermal stability was reduced, the daylily fragrance was lost too quickly, and it was difficult to achieve a long-lasting antibacterial effect.
[0055] In Comparative Example 1, the wear-resistant component was only a mixture of dopamine-modified aramid fibers and anhydrous ethanol. The aramid fibers without added tetraethyl orthosilicate did not generate nano-silica on the surface. Therefore, both the wear resistance and hydrophobicity were reduced.
[0056] This specific embodiment is merely an explanation of this application and is not intended to limit it. Based on the above description, those skilled in the art can make various changes and modifications without departing from the technical concept of this application. The technical scope of this application is not limited to the contents of the specification but must be determined according to the scope of the claims.
Claims
1. A microcirculation therapy pad, characterized in that: The device includes a physiotherapy component and a fabric component. The fabric component covers the exterior of the physiotherapy component and includes a wear-resistant layer, a graphene air layer, a graphene fiber layer, a silk-like cotton layer, a brushed fabric layer, a needle-cotton layer, a sponge layer, and a mesh breathable layer. The physiotherapy component is located between the brushed fabric and the needle-cotton fabric. The wear-resistant layer is formed by coating the surface of the graphene air layer with a wear-resistant coating, which comprises the following components in parts by weight: 500-560 parts of coating substrate, 60-70 parts of antibacterial sustained-release microcapsules, 120-160 parts of abrasion-resistant component, 12-16 parts of softener, and 10-16 parts of defoamer; The wear-resistant components include aramid fibers, dopamine, and silica; The wear-resistant component is prepared by the following method: Nano-aramid fibers were mixed with deionized water to obtain an aramid fiber dispersion. Dopamine was added, and the pH was adjusted to alkaline. The mixture was stirred and reacted. After the reaction, the mixture was washed to obtain dopamine-modified aramid fibers. The dopamine-modified aramid fibers were mixed with anhydrous ethanol, and ammonia was added. The mixture was sonicated, and the temperature was increased while stirring. Tetraethyl orthosilicate and 1H,1H,2H,2H-perfluorodecyltriethoxysilane were added while stirring. The mixture was stirred for 4 hours. Then, 1H,1H,2H,2H-perfluorodecyltriethoxysilane was added and the mixture was stirred for 3 hours to obtain the wear-resistant component. The antibacterial sustained-release microcapsules include daylily flavoring, polyvinyl alcohol, and ε-polylysine; The antibacterial sustained-release microcapsules were prepared using the following method: Daylily fragrance was mixed with isophorone diisocyanate to obtain an oil phase. Polyvinyl alcohol was mixed with deionized water to obtain a polyvinyl alcohol dispersion. The polyvinyl alcohol dispersion was heated to the reaction temperature, and the oil phase was added to the polyvinyl alcohol dispersion. Emulsifiers and chain extenders were added and stirred to obtain a daylily fragrance pre-microcapsule emulsion. ε-polylysine was mixed with deionized water to obtain an ε-polylysine aqueous solution. The ε-polylysine aqueous solution was added to the daylily fragrance pre-microcapsule emulsion, and the reaction was carried out while maintaining the reaction temperature and stirring to obtain antibacterial sustained-release microcapsules. The mass ratio of the aramid fiber to dopamine is 1:(1.12-1.18); The mass ratio of the dopamine-modified aramid fiber to tetraethyl orthosilicate is 1:(0.45-0.49); The mass ratio of daylily fragrance, polyvinyl alcohol and ε-polylysine is 1:1.1:(0.69-0.75); The reaction temperature is 50-60℃.
2. The microcirculation therapy pad according to claim 1, characterized in that: The emulsifier includes Tween-80.
3. The microcirculation therapy pad according to claim 1, characterized in that: The wear-resistant coating is prepared by the following method: The coating substrate, antibacterial slow-release microcapsules, abrasion-resistant components, softener and defoamer are mixed and stirred to obtain an abrasion-resistant coating.
Citation Information
Patent Citations
Efficient graphene physiotherapy cushion and production method
CN112841996A
Antibacterial coating essence microcapsule and method
CN116411460A